Didactic adaptation of forms, methods, techniques, methods of independent cognitive activity in the paradigm of high school student – a student of higher academic institutions (Pedagogy of Higher and Secondary Education, 2013)
Polyakova V. Y. Didactic adaptation of forms, methods, techniques, methods of independent cognitive activity in the paradigm of high school student – a student of higher academic institutions.Didactic adaptation of forms, methods, techniques, methods of independent cognitive activity in the paradigm of high school student - a student of higher academic institutions as one of the conditions for the organization of teaching self-learning activities of students of high school is considered on the basis of psycho-pedagogical analysis.
Keywords: didactic adaptation; forms; methods; techniques; methods of self-educational activities; self- educational activity; the organization of independent educational activities